Prevalence of Contralateral Hip Abductor Tears and Factors Associated With Symptomatic Progression. Issue 6 (May 2022) - Arvesen, John; McCallum, Jeremy; Pill, Stephan G.; Cannady, Holly; Adams, Kyle J.; Jackson, Isaiah; Wienke, Jeffrey R.; Folk, Jason
Background: Patients with gluteus medius tendinopathy present with laterally based hip pain that can be diagnosed under the greater trochanteric pain syndrome diagnosis. Magnetic resonance imaging (MRI) can assist in diagnosing pathology of the symptomatic hip, and when a pelvic MRI that includes both hips, the clinician may identify asymptomatic tears in the nonsurgical hip. In patients who undergo unilateral gluteus medius repairs, little is known about the prevalence or subsequent onset of clinical symptoms in the nonsurgical hip. Purpose: To describe (1) the prevalence of asymptomatic contralateral gluteus medius tears in patients with unilateral symptoms, (2) the presentation and time before symptom onset, and (3) the morphological characteristics on MRI of future symptomatic tears. Study Design: Case series; Level of evidence, 4. Methods: A total of 51 consecutive patients who underwent gluteus medius tear surgery were reviewed for contralateral hip pathology; of these, 43 patients were 2 years out from index surgery with reviewable preoperative MRI scans. A musculoskeletal radiologist reviewed the MRI scans for tear size, tendon retraction, and fatty infiltration using the Goutallier-Fuchs grading system. Medical record review identified contralateral hips requiring subsequent treatment. Results: Of the original 43 patients, 10 (23%) had no contralateral tear, 19 (44%) had low-grade partial tears, 9 (20%) had high-grade partial tears, and 5 (11%) had full-thickness tears. Thirty-seven patients had unilateral symptoms; the other 6 had mild contralateral hip pain at enrollment. Of the 37 patients with unilateral symptoms, 27 (73%) had a contralateral tear; of those, 10 became symptomatic at an average of 24 months after index presentation (range, 6-50 months). In patients with symptomatic progression, 7 had low-grade partial tears, 1 had a high-grade partial tear, and 2 had full-thickness tears, with an average retraction of 17 mm. Tendon tear grade on MRI did not always correlate with symptoms or future presentation. All symptomatic progression remained mild to moderate. Seven patients required a corticosteroid injection, and none needed contralateral hip surgery within 2 years. Conclusion: Of patients who underwent surgery for a gluteus medius tear, 73% (27/37) had an incidental MRI-confirmed contralateral hip abductor tear. Of these, 37% (10/27) developed symptoms consistent with greater trochanteric pain syndrome during the 2-year study period.